DIFFERENTIATION AND INDIVIDUALISATION - A MUST IN THE TRAINING OF TALENTED SPORTSMEN (GYMNASIUM, 2009)
The path to the top sporting result in handball is long and difficult; it is open only to individuals thathave above average motor and physical abilities, suitable and unvarying personal characteristics, moralqualities and other mental aptitudes. External factors, such as organisational and expertise level of the cluband coach, also influence the development and success. The beginning and an important part of this path isrepresented with the training of children and youth and a question: Will the sport of young people utilize itsenormous educational potential and turn talents into stars, who will keep winning and at the same time stayhappy? It is possible, yet the incorrect approach can result in the loss of handball talents or become a sourceof negative experiences, stress and pressure. Largely, this depends on a discipline, policy of the sports clubs,associations and society in general; yet mostly it depends on a coach who has daily contact with players inthe training process. Handball training is carried out in groups that are usually very heterogeneous andrequire specific type of work. Differentiation and individualisation are coaching methods for working with adiverse group of handball players. A coach can achieve this by precise organisation of training, which allowspractising various exercises within a specific individual task. It is also recommended that several coaches orspecialist coaches participate in the work with the youngest age categories.